Parametric Modeling & Study Of Structural Characterics Of Wind Turbine Blade (International Journal of Engineering and Computer Science, 2015)
The structural aspects of a long blade in a an up wind, horizontal-axis wind turbine were hybrid composite structure using glass and carbon fiber plies was created yielding a light-weight  design  with  a  low  tip deflection. The results confirmed the design to have acceptable performance with regard to tip deflection, maximum and minimum strains, and a critical load. Detailed descriptions  of  the  structural  components and ply layups are presented along with resulting  maximum  and  minimum  strains and deflections. In addition, optimization techniques   were   introduced   to   provide insight for future studies with the blade a detailed  review  of  current  state  of  art  for wind turbine blade design is presented. A design  different  airfoil  cross  section  (‘I’,‘C’, Double ‘C’).and Structural analysis, FatigueCharacterics of Wind Turbine Blade.